Transient modeling of a flash tank vapor injection heat pump system – Part II: Simulation results and experimental validation. (January 2015) - Qiao, Hongtao; Xu, Xing; Aute, Vikrant; Radermacher, Reinhard
Abstract: This two-part article investigates the transient characteristics of a flash tank vapor injection system through modeling and experimental validation. The first part describes the detailed modeling techniques for each component, and the second part describes the transient simulations that are carried out for the overall system under start-up and shut-down operations and presents the results. After comparing the predictions of the proposed model with the experimental data, it was concluded that the proposed model can adequately capture the transient heat transfer and flow phenomena of the system. The dynamic system response when subjected to a step change in the opening of the upper-stage EEV (electronic expansion valve) was also investigated. It was found that EEV opening has a significant impact on the system performance and the liquid level in the flash tank, but exhibits little effect on the suction pressure. These findings were corroborated through experiments. Highlights: Transients of a flash tank vapor injection system at start-up. Transients of a flash tank vapor injection system at shutdown. The effects of the step change in the upper-stage EEV opening are investigated. Upper-stage EEV opening has a crucial impact on system performance. Upper-stage EEV opening exhibits little effect on the suction pressure.